Effect of glass-fiber post on the biomechanical behavior of teeth with direct veneers - Jurema, Ana Luiza Barbosa; Penteado, Marcela Moreira; Tribst, João Paulo Mendes; Caneppele, Taciana Marco Ferraz; Borges, Alexandre Luiz Souto (Brazilian Dental Science, 2020)
Objective: This study aimed to evaluate the biomechanical behaviour of endodontically treated teeth with direct veneer that received or not intra-radicular glass fiber post by finite elements analysis. Material and methods: Six models were designed, varying the presence or absence of glass fiber post and the thickness of direct veneer (0.5, 0.7 and 1 mm). Tridimensional models of maxillary central incisors were obtained with CAD software, Rhinoceros 4.0, and transferred to CAE software, ANSYS 17.2, which a 100N load was applied in a 45° on the lingual surface to simulate functional movements. Geometry contacts were bonded, and the structures were isotropic, linear, elastics, and homogeneous. After coherence and convergence analysis of mashes, the chosen fail criterion was the maximum principal stresses. Results: For cement, glass fiber post, the stress distribution was similar independently of glass fiber post presence or veneer thickness. Models with glass fiber post had better stress distribution and lower values of maximum stress for inner dentin and veneers. Veneers with 0.5 and 1 mm had higher stress concentration areas. Conclusions: It can be concluded that glass fiber post is favorable for restored teeth with direct veneers, and very thin or very thick preparations can damage the biomechanical behavior of restorations. Keywords Dental veneers; Finite element analysis; Nonvital tooth; Post and core technique.